A survey of treatment practices in management of chronic urticaria patients among dermatologists of India - B M Shashi Kumar; Savitha A Somaiah; Swathy Prasannan (Wolters Kluwer Medknow Publications, 2024)
Introduction: Chronic spontaneous urticaria (CSU) is a frequent problem encountered by dermatologists where treatment response is often unsatisfactory. This exerts a heightened responsibility on dermatologists to tailor their treatments according to each patient. Aims: The aim of the present study was to evaluate the therapeutic, diagnostic approaches of Indian dermatologists to CSU patients and the need to further generate a base for the creation of Indian urticaria guidelines. Materials and Methods: A questionnaire-based survey was conducted among practicing dermatologists of India. Conclusions: At the end of this questionnaire-based study, we concluded that there is a wide variation in the treatment practices among practicing dermatologists of India.